Use of mobile phones for academic purposes by law students of Igbinedion University, Okada (2015)
Extensive literature review has shown that the 21st century youth is techno savvy, hence spend quality time surfing the internet using their internet enabled phones. This paper intends to investigate the extent to which students of the College of Law, Igbinedion University use their mobile phones for the purpose of helping them get academic information. The paper investigates how often the students use the internet on their mobile phones and what interest them most on the internet. It aims to determine how often they visit the internet for academic purpose. Five research questions were determined and tested with questionnaire serving as the main instrument for data collection. A total of 150 questionnaires were distributed and all 150 were duly filled and returned, out of which 148 was found usable, representing 98.7% of the representative total population. The analysis of the students ‘perception showed that majority of the students use their mobile phones to search for academic information. The paper also finds out that after academic information, the next highly used function of the mobile phone is for social networking, chatting and reading the news online. It concludes by recommending introduction of mobile learning in the university.